PENGEMBANGAN KURIKULUM PTAI YANG TERKAIT DAN SEPADAN DENGAN KURIKULUM MADRASAH - Syafruddin Nurdin (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2009)
One of the most important agenda of in education todai is to establish such a link-and-match curriculum among levels or educational institution and among educational institution, workfield, and stakeholders. To realize such a desired curriculum among levels or educational institution, the visions, missions, curriculum and characteriustics of the instituions should be comprehensively understood. The process of the curriculum development may follow the following steps: (1) identifying factors or determinats that contribute to the curriculum development and conducting need analysis as well, (2) identifying the desired competency and profile of the graduates, (3) deciding knowledge, affection, and skills which are neede to build such competency, (4) designing the structure of the curriculum and establishing link and match, and (5) developing syllabus. In developing curriculum, especially in achieveing a link-and-match curriculum, the following principles should be implemented: relevance, continuity and integration.Kata Kunci: pengembangan kurikulum, kurikulum madrasah